Strategic management : - Pearce II, John A. (McGraw - Hill, 2007)
Contemporary research in strategic management, with an emphasis on conceptual tools and skills created by scholars and practitioners in the field are evident throughout this 12-chapter book. The book is completed with multiple Business Week and traditional strategic management cases. Pearce and Robinson’s Strategic Management presents a unique pedagogical model created by the authors. Instructors who desire quantitative analysis will like the financial data available here. The new, strong coverage of Business Week material provides a currency and uniqueness to the text. --This text refers to the Hardcover edition.